A novel identified circular RNA, circ_0000491, aggravates the extracellular matrix of diabetic nephropathy glomerular mesangial cells through suppressing miR-101b by targeting TGFβRI - Mou, Xin (Mol Med Rep, 2020)
Circular RNAs (circRNAs) have crucial roles in various diseases; however, the mechanisms of action underlying circRNAs in the occurrence and development of diabetic nephropathy (DN) remains largely unknown. The present study investigated the differentially expressed circRNAs in the DN mice kidney cortex using circRNA sequencing and elucidated the role of circRNAs in mesangial cells. It was revealed that 40 circRNAs were unconventionally expressed, including 18 upregulated circRNAs and 22 downregulated circRNAs. Furthermore, circ_0000491 levels were significantly augmented in both DN mice and high glucose (HG, 30 mM)-induced mouse mesangial cells (MES13 cells). Knockdown of circ_0000491 significantly suppressed the increase of vimentin, fibronectin and α-smooth muscle actin, as well as collagen type I, III and IV, whilst reversing the decrease of E-cadherin in HG-induced MES13 cells. It was further revealed that circRNA_0000491 sponged miR-101b and that miR-101b directly targets TGFβRI. In addition, the expression levels of miR-101b were negatively associated with the transcriptional level of circRNA_0000491 and miR-101b inhibitors reversed the suppression of extracellular matrix (ECM)-associated protein synthesis mediated by knocking-down circRNA_0000491. In conclusion, the present study investigated the circRNA_0000491/miR-101b/TGFβRI axis in ECM accumulation and fibrosis-associated protein expression levels of mesangial cells, which suggested that circRNA_0000491 may be beneficial for the development of an effective therapeutic target for DN.